The Critical Role of Potassium Efflux and Nek7 in Pasteurella multocida-Induced NLRP3 Inflammasome Activation - Wang, Yu; Zeng, Zheng; Ran, Jinrong; Peng, Lianci; Wu, Xingping; Ye, Chao; Dong, Chunxia; Peng, Yuanyi; Fang, Rendong (Frontiers in Microbiology, 2022)
Pasteurella multocida is a zoonotic pathogen causing respiratory infection in different animal species such as cattle, sheep, pigs, chickens and humans. Inflammasome is a complex assembled by multiple proteins in the cytoplasm and plays an important role in the host defense against microbial infection. Bovine Pasteurella multocida type A (PmCQ2) infection induces NLRP3 inflammasome activation and IL-1β secretion, but the mechanism of PmCQ2-induced activation of NLRP3 inflammasome is still unknown. Therefore, the underlying mechanism was investigated in this study. The results showed that potassium efflux mediated PmCQ2-induced IL-1β secretion and blocking potassium efflux attenuated PmCQ2-induced caspase-1 activation and ASC oligomerization. Furthermore, NIMA-related kinase 7 (Nek7) was also involved in PmCQ2-induced caspase-1 activation and IL-1β secretion. In addition, PmCQ2 infection promoted Nek7-NLRP3 interaction, which is dependent on potassium efflux. In conclusion, our results indicate the critical role of potassium efflux and Nek7 in Pasteurella multocida-induced NLRP3 inflammasome activation, which provides useful information about Pasteurella multocida-induced host immune response.